Interproximal Papillae Reconstruction around Implant Using Subepithelial Connective Tissue Graft in Maxillary Anterior Region: A Case Series - Satish Gupta; Vikas Deo; Cecil Williams (eJournal of Oral Maxillofacial Research, 2012)
Objectives: The present study was undertaken to evaluate the effectiveness of interproximal papillae reconstruction around early loaded single implant using subepithelial connective tissue graft in maxillary anterior region.Material and Methods: Ten systemically healthy patients (mean age = 29.3 [SD 7.9] years) in need of dental implants in maxillary anterior region were included in the study. Interproximal papillae reconstruction around single implant using subepithelial connective tissue graft was applied. The donor palatal tissue was harvested by a ‘trap door approach’. Subepithelial connective tissue graft was inserted in the pouch created on mesial and distal site of implant. Clinical and radiographic parameters were recorded around the each implant, including papillary height and papillary gingival contour, at baseline, 3 and 6 months after operation. Results: The mesial papilla height was increased by 1.9 (SD 0.87) mm, P = 0.005 at 3 month and maintained at 1.5 (SD 0.97) mm, P = 0.007 at 6 months. The distal papilla height was increased by 2 (SD 0.66) mm, P = 0.004 at 3 month and maintained at 1.2 (SD 0.78) mm, P = 0.010 at 6 months. Assessment of papilla contour index showed 90% aesthetic success both for mesial and distal papilla at 6 months.Conclusions: It can be concluded that subepithelial connective tissue graft may be used to successfully augment the gingival papillae adjacent to single tooth implant restoration.